Bathrips in China (Thysanoptera: Thripidae), with a new record and new synonym - Mirab-Balou, Majid; Yang, Shu-Lan; Tong, Xiao-Li (Zootaxa, 2012)
Bathrips Bhatti (1962) currently includes three species, all from the Oriental region. The systematic relationships of this genus remain equivocal. Mound & Masumoto (2004) pointed out the similarity in general appearance of the species to those of Trichromothrips, but Masumoto & Okajima (2005) did not include Bathrips in the Trichromothrips genus-group. The species of Bathrips lack the dorso-apical setae on the first antennal segment that characterize the Trichromothrips group, and tergite IX of males bears a median pair of short and stout setae (Masumoto & Okajima 2005). Bathrips was distinguished originally from Taeniothrips on the basis of a different fore wing chaetotaxy, but the complete absence of a comb on tergite VIII suggests that these two are not related.